The Relationship between Family Support and Self-Care Behavior on Diabetes Mellitus Patients - Endang Mawarti Sihotang; Tini; Edi Purwanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Diabetes Mellitus is a non-communicable disease which is a global health problem with a control strategy that requires patient independence in self-care. This study aims to determine the relationship between family support and self-care behavior in Diabetes Mellitus patients in the Working Area of ​​UPT Puskesmas Tubaan. This research is a type of correlational quantitative research with a cross sectional design. There is a significant relationship between family support and self-care behavior in Diabetes Mellitus patients in the Working Area of ​​UPT Puskesmas Tubaan (p-value = 0.006). So it can be concluded that family support with low Diabetes Mellitus patients is 2 times more likely to result in low self-care behavior. It is necessary to take a family approach so that the patient is able to get family support to achieve better self-care behavior.